Instytucja odpowiedzialności państwa za szkody wyrządzone przez funkcjonariuszy – czy współcześnie obowiązujące porządki prawne zapewniają skuteczną (prawną i sądową) ochronę poszkodowanemu i państwu? – kilka uwag na temat prawa niemieckiego, polskiego or - Krygier, Agata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The institution of State’s liability for detrimental acts of officials has its roots in ancient legal systems, especially in Roman law. Due to the fact that the Romans did not recognize the State as the legal person in today’s meaning, it clearly explains why a guilty official (lat. magistratus) bore personal liability for damage caused in exercising his duties. In this legal system the State completely protected its interests while the victims could only sued some of guilty magistrates what it did not guarantee them (i.e. the vicitims) effective (legal and judicial) protection. Over centuries, the institution has gradually evaluated from magistrate’s personal liability to the State’s liability (i.a. in Germany and in Poland). Nowadays, scholars and practising lawyers ponder over if binding provisions in both countries give effective (legal and judicial) protection for detrimental acts of officials: the victims against the State on the one hand and the State against the deliquent official on the other hand. It seems that there are no so many doubts about the victim’s protection, what it cannot be said in relation to the protection of the State’s interests. It is also interesting how this institution functions in the European Union? Because of the fact that the institution of the State’s liability, and in particular its effectiveness, is widely discussed in legal community, the main aim of the author is to take an attempt to answer the question which is posed in the topic.